2019
DOI: 10.1590/1980-549720190005
|View full text |Cite|
|
Sign up to set email alerts
|

Análise da qualidade da informação sobre mortalidade por homicídio a partir dos óbitos com intenção indeterminada. Bahia, Brasil, 2002-2013

Abstract: RESUMO: Objetivo: Identificar padrões na distribuição espacial das taxas de mortalidade por homicídio, considerando a proporção de óbitos de intenção indeterminada nos municípios do Estado da Bahia, no período de 2002 a 2013. Método: Foi realizado um estudo ecológico, utilizando os dados do Sistema de Informação sobre Mortalidade (SIM). A mortalidade proporcional de intenção indeterminada sobre o total de causas externas e a taxa de homicídio foram analisadas, nos diversos municípios baianos e considerando a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
0
0
2
Order By: Relevance
“…This is consistent with the results of a study exploring HIV knowledge in a sample of MSM in South Africa and in the United States, which showed a high level of knowledge among MSM living in both countries [ 24 ]. However, another study conducted in the UK reported a low level of knowledge among black and minority ethnic MSM [ 25 ], and this finding is superimposable to the results of other similar studies conducted in low-income or middle-income countries [ 26 , 27 ]. Reasonably, in high-income countries and among people with a higher social status, HIV knowledge and awareness are adequate, especially in the population at high risk of infection, like MSM.…”
Section: Discussionsupporting
confidence: 53%
“…This is consistent with the results of a study exploring HIV knowledge in a sample of MSM in South Africa and in the United States, which showed a high level of knowledge among MSM living in both countries [ 24 ]. However, another study conducted in the UK reported a low level of knowledge among black and minority ethnic MSM [ 25 ], and this finding is superimposable to the results of other similar studies conducted in low-income or middle-income countries [ 26 , 27 ]. Reasonably, in high-income countries and among people with a higher social status, HIV knowledge and awareness are adequate, especially in the population at high risk of infection, like MSM.…”
Section: Discussionsupporting
confidence: 53%
“…Ressaltasse que na população jovem, a mortalidade por essas causas representa números alarmantes. No Brasil, esses óbitos crescem anualmente caracterizando um problema de saúde pública (Silva et al, 2010), sendo a primeira causa de mortalidade entre adultos jovens, a partir da primeira década de vida (Souza, Souza & Pinto, 2019) .…”
Section: Introductionunclassified
“…Surpreendentemente, nenhum caso foi encontrado registrado em todas as bases investigadas.Romero et al, 2019 32 Estudo Ecológico. Analisar a tendência e a desigualdade na completude da raça/cor dos óbitos de idosos no SIM entre 2000 e 2015 no Brasil.Em geral, a variável raça/cor no Sistema de Informações sobre Mortalidade é de qualidade suficiente para estudos sobre desigualdade na mortalidade de idosos, com algumas exceções no nível municipal Souza et al, 2019.. Fonte: O acesso e a qualidade das bases de dados e sistemas de informações em saúde no Brasil: Revisão de escopo (2024).Legenda: NR= Não pode ser respondido; NA = Não aplicável; R = Resultado.…”
unclassified